Bariatric Surgery versus Intensive Medical Therapy for Diabetes — 5-Year Outcomes - Schauer, Philip R; Bhatt, Deepak L; Kirwan, John P; Wolski, Kathy; Aminian, Ali; Brethauer, Stacy A; Navaneethan, Sankar D; Singh, Rishi P; Pothier, Claire E; Nissen, Steven E; Kashyap, Sangeeta R (The New England journal of medicine, 2017)
Five-year data showed that among patients with type 2 diabetes and a BMI of 27 to 43, bariatric surgery plus intensive medical therapy was more effective than intensive medical therapy alone in decreasing or resolving hyperglycemia, even among those with a BMI of less than 35. Observational studies 1 – 6 and randomized, controlled trials, which have generally been short-term studies, 7 – 19 have shown that bariatric surgery, when used specifically to treat diabetes, significantly improves glycemic control and reduces cardiovascular risk factors. In the Surgical Treatment and Medications Potentially Eradicate Diabetes Efficiently (STAMPEDE) trial, we reported that, at 1 year and 3 years after randomization, both gastric bypass and sleeve gastrectomy were superior to intensive medical therapy alone in achieving excellent glycemic control (i.e., glycated hemoglobin ≤6.0%), reducing cardiovascular risk, improving quality of life, and decreasing medication use. 8 – 10 The current article provides results of the final, 5-year . . .